Sanguisorba officinalis L. enhances the 5-fluorouracil sensitivity and overcomes chemoresistance in 5-fluorouracil-resistant colorectal cancer cells via Ras/MEK/ERK and PI3K/Akt pathways - Weijia Zhang; Ling Ou; Chang Peng; Shuyi Sang; Zhong Feng; Yuanjing Zou; Yuemei Yuan; Hao Li; Guimin Zhang; Meicun Yao (Heliyon, 2023)
Sanguisorba officinalis L., a traditional Chinese medicine (TCM) called DiYu (DY) in China, has a strong tradition of utilization as a scorching, blood-cooling, and hemostatic medication, and was used for cancer prevention and treatment due to its potential immune-enhancing and hematological toxicity-reducing effects. Previous studies have reported significant effects of DY on cancers including colorectal cancer (CRC), which is one of the most common malignancies worldwide. The first-line cure 5-fluorouracil (5-FU) plays decisive commerce in the sedative of CRC as a clinically available chemotherapeutic agent. One of the primary causes of cancer treatment failure is the acquisition of chemotherapy drug resistance. In order to successfully combat the emergence of chemoresistance, it is essential to identify herbs or traditional Chinese medicine that have adjuvant therapeutic effects on CRC. Therefore, this study aimed to determine whether DY could improve the sensitivity, conquer the chemoresistance of 5-FU-resistant CRC cells, and investigate its intrinsic mechanism. Materials and methods: MTT, Hoechst 33258 staining, and flow cytometry assays were used to determine the anticancer activity of DY alone or in combination with 5-FU against 5-FU-resistant CRC cells (RKO-R and HCT15-R) and wound healing assays were conducted to detect cell migration. Transcriptomic techniques were carried out to explore the effect and mechanism of DY on drug-resistant CRC cells. Western Blot and RT q-PCR assays were performed to validate the mechanism by which DY overcomes drug-resistant CRC cells. Results: These results indicated that DY alone or in combination with 5-FU significantly inhibited the proliferation and the migration of resistant CRC cells, and potentiated the susceptibility of 5-FU to drug-resistant CRC cells. GO and KEGG enrichment analysis showed that the mechanisms of drug resistance in CRC cells and DY against drug-resistant CRC cells highly overlapped, involved in the modulation of biological processes such as cell migration, positive regulation of protein binding and cytoskeleton, and MAPK (Ras-ERK-MEK), PI3K/Akt, and other signaling pathways. Moreover, DY can mediate the expression of p-R-Ras, p-ERK1/2, p-MEK1/2, p-PI3K, p-AKT, HIF-1A and VEGFA proteins. In addition, DY significantly suppressed the expression of AKT3, NEDD9, BMI-1, and CXCL1 genes in resistant CRC cells. Conclusion: In conclusion, DY could inhibit the proliferation and migration of 5-FU-resistant cells and strengthen the sensitivity of 5-FU to CRC-resistant cells. Furthermore, DY may prevail over chemoresistance through the Ras/MEK/ERK and PI3K/Akt pathways. These findings imply that DY may be a potential drug for clinical treatment or adjuvant treatment of drug-resistant CRC.